2020
DOI: 10.3389/fevo.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Sublethal Pesticide Exposure on Honey Bees: A Role for Probiotics as Mediators of Environmental Stress

Abstract: Managed populations of the European honey bee (Apis mellifera) support the production of a global food supply. This important role in modern agriculture has rendered honey bees vulnerable to the noxious effects of anthropogenic stressors such as pesticides. Although the deleterious outcomes of lethal pesticide exposure on honey bee health and performance are apparent, the ominous role of sublethal pesticide exposure is an emerging concern as well. Here, we use a data harvesting approach to better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 214 publications
(265 reference statements)
0
72
0
Order By: Relevance
“…More recently, however, several laboratory studies reported sublethal effects of the herbicide at the individual bee level. Such effects are of current concern, as they can reduce honey bee reproduction, immunity, cognition, and overall physiological functioning, leading to a suboptimal honey bee performance and population decline [ 15 ]. For GBH, impaired cognitive abilities and navigation skills [ 16 , 17 ], and, primarily, implications for the host-microbiome were indicated [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, several laboratory studies reported sublethal effects of the herbicide at the individual bee level. Such effects are of current concern, as they can reduce honey bee reproduction, immunity, cognition, and overall physiological functioning, leading to a suboptimal honey bee performance and population decline [ 15 ]. For GBH, impaired cognitive abilities and navigation skills [ 16 , 17 ], and, primarily, implications for the host-microbiome were indicated [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, despite susceptibility or resistance, OTC is unable to treat P. larvae spores in the comb, which can act as a source of reinfection. To address these issues and guard against the potentially rapid evolution of resistance, it is prudent to test alternative control measures, which so far include hygienic breeding 12 , use of bioactive essential oils 13 , bacteriophage therapy 14 , synthetic indoles with anti-germination properties 15 , and supplementation of hives with lactic acid bacteria [16][17][18] . The promise of this latter approach is up-held by studies demonstrating that lactobacilli can promote insect innate immunity and detoxification [19][20][21] , extend longevity of adult honey bees 22 , and stimulate queen brood production 23,24 .…”
mentioning
confidence: 99%
“…Tank mixes can increase total mortality in honey bees in predictable (Pilling & Jepson 1993;Iwasa et al 2004;Wernecke et al 2019) and unpredictable ways Zhu et al 2014;Wade et al 2019). Despite their relevance under normal eld conditions, these aspects of pesticide toxicology are often overlooked (Chmiel et al 2020). Most emphasis has focused on formulations and their active ingredients rather than on the adjuvants that can be added to the spray solution.…”
Section: Introductionmentioning
confidence: 99%